Factors affecting audience share of ABS-CBN'S WOWOWEE and GMA'S EAT BULAGA in Barangay Mintal, Davao City - Abrio, Doyle Felix T.
Noontime shows are among the to top-rated shows in the Philippines. However, there is a disparity in the results of audience surveys from Mega manila and Davao City. Wowowee has higher ratings than eat bulaga in Davao City in contrast to what Mega Manila results show. This study aimed to see whether the factors that affect audience choice that McQuail presented in his integrated model of the process of media choice leads to the preference of one show over another. This study also liked to know whether media issues affect Davao City audiences' TV viewing habits and preferences. The results of this survey showed the factors provided by McQuail affects media choice. These factors were media availability, publicity, timing, presentation and issues. It is also found out that the media issues didn't significantly changed the audiences' TV viewing habits and preferences. It also found out that watching show from one network for a long time leads to preference to the same network. This recommends that the producers of noon time shows should provide shows that meet the needs of the viewers provided by this study. It also recommends further studies upon this matter at other places in Davao City.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts